840 Obstructive to Central: A switch in sleep apnea type after arteriovenous malformation rupture. (3rd May 2021) - Greer, Meredith; Trotti, Lynn Marie; Collop, Nancy
Abstract: Introduction: Sleep apnea and stroke have long been shown to be linked, with sleep apnea increasing the risk for stroke and stroke leading to sleep apnea. When the latter occurs, it can present as central sleep apnea (CSA), often in the form of Cheyne-Stokes breathing (CSB), and has been shown to resolve over time. We present a patient with persistent CSA after severe hemorrhagic stroke secondary to rupture of a temporal/thalamic arteriovenous malformation (AVM). Report of case(s): A 33-year-old man with a history of obstructive sleep apnea (OSA) presented to our clinic for re-evaluation of his disease. He was diagnosed with OSA in 2006 at which time he was 270 pounds with a body mass index (BMI) of 36.7, thus the OSA was thought to be secondary to obesity. When he presented to our clinic 10 years later, he had lost approximately 80 pounds after suffering multiple strokes. In 2014, he had a left temporal lobe hemorrhage due to rupture of a left temporal/thalamic AVM and required decompressive hemicraniectomy. In 2015, he had a re-bleed of this AVM, with new hemorrhage extending inferiorly into the left cerebral peduncle and pons, and superiorly into the left parietal periventricular white matter anteriorly along the optic tract. Ultimately, he was treated with stereotactic radiotherapy to the AVM nidus with no residual AVM. However, he has chronic encephalomalacia of the left basal ganglia, thalamus, temporal, parietal, and occipital lobes with extension into the left cerebral peduncle and changes consistent with radiation necrosis. His residual symptoms are aphasia and right-sided hemiplegia and although his snoring resolved with weight loss, his mother noticed pauses in his breathing overnight. A repeat sleep study done in 2016 showed 27 central apneas and 0 obstructive apneas with an AHI of 5.4 events/hour. He was subsequently studied on ASV with residual AHI of 0.4 events/hour. Conclusion: Although patients with OSA may be at higher risk for stroke, it is important to re-evaluate their sleep apnea after such an event to ensure appropriate diagnosis and treatment going forward. Support (if any):